TRANSFORMING PERIMENOPAUSAL HEALTH: NUTRITIONAL AND MOVEMENT-BASED INTERVENTIONS - Vohra, Aditi; Kaur, Tarvinder Jeet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Perimenopause, a transitional phase preceding menopause, signifies a decline in estrogen levels, often manifesting in one's 40s or even 30s, with associated symptoms such as irregular menstrual cycles, hot flashes, mood swings, and altered body composition. These symptoms not only affect quality of life but also pose long-term health risks, including cardiovascular disease, hypertension and osteoporosis. Given the complex hormonal changes during perimenopause, effective interventions are imperative. This study in Ambala, Haryana, aimed to assess the impact of dietary and physical activity interventions on perimenopausal women's health. Fifty women aged 35 to 50, self-reporting perimenopause, underwent a three-month intervention. The experimental group received tailored nutrition and movement guidance, while the control group maintained their usual lifestyle. Noteworthy enhancements were observed in dietary habits, anthropometric measurements, and biochemical parameter in the experimental group. These improvements included increased intake of nutrient-rich foods, reduction in weight, BMI, WC, HC, WHR and improvements in perimenopausal symptoms and related biochemical marker like hypertension. These findings underscore the efficacy of personalized interventions in mitigating perimenopausal symptoms and improving overall health, emphasizing the importance of lifestyle modifications during this transitional phase. This study investigates the effects of dietary and exercise interventions on physical health markers, dietary habits, physical activity levels, BMI and biochemical assessment of perimenopausal women. By exploring the impact of lifestyle modifications, the research aims to alleviate symptoms, enhance quality of life and reduce the risk of lifestyle diseases during this transitional phase.